Edible Aerodramus fuciphagus bird nest for wound healing: In search of the best extraction method to increase sialic acid and its relationship with collagen production - Supamas Napavichayanun; Rungnapha Yamdech; Narendra Reddy; Pornanong Aramwit (Agriculture and Natural Resources, 2021)
Edible Aerodramus fuciphagus bird nest (EBN) has several biological properties, especially wound healing promotion. However, better extraction methods are required to increase the level of sialic acid, which is the major factor determining EBN quality. Furthermore, the relationship between sialic acid and collagen production has not been reported. Therefore, this study evaluated the effect of the source and extraction method on EBN quality to identify the best extraction method to maximize sialic acid in EBN. One-way analysis of variance was used for comparisons of results. In the comparison of EBN types, EBN from houses not only contained higher amounts of sialic acid and protein than those from caves, but the antioxidant activity also seemed to be superior to cave EBN. This study found a new combination of acid and thermal extraction that increased the amount of sialic acid compared to single extraction (mean ± SD = 17.77 ± 1.33 mg/g and 5.41 ± 1.06 mg/g, respectively; p < 0.05). The higher amount of sialic acid resulted in a higher amount of collagen production and the mean (± SD) level (1.81±0.21 ×104 μg/cell) was significantly (p < 0.05) higher than that of the control (1.55 ± 0.18 ×104 μg/cell). Furthermore, the extract had a positive effect on L929 fibroblast cell growth and cell migration that are vital factors in wound healing. This straightforward extraction method can be applied for use in large EBN facilities.